RADIOCARON DATA OF FUNERARY DESCOVERIES FROM MIDDLE BRONZE AGE IN THE MUREȘ VALLEY. THE WIETENBERG CEMETERY FROM LIMBA-OARDA DE JOS (ALBA COUNTY, ROMANIA) - Marius-Mihai Ciută; Colin P. Quinn; Radu V. Totoianu (Journal of Ancient History and Archaeology)
The archaeological rescue excavations occasioned by the construction of the Lot no. 1 of the Highway no. 10, Sebeș-Turda, highlighted an unexpected Bronze Age necropolis belonging to Wietenberg Culture. The Bronze Age necropolis was delimited between 6+600 and 6+650 kilometers, and located on the southwestern part of the Site no. 6, right above the early Vinča settlement defensive trenches (Fig. 1-2). With 74 excavated funerary complexes, the partially excavated Wietenberg cemetery is one of the largest in Transylvania. According the radiocarbon data presented in this study, the necropolis was used  in the Middle Bronze Age (1780-1690 cal. BC), associated with the Wietenberg culture (phase II), and is contemporary with the end of the cemetery from Sebeș-Între Răstoace located approximately 7.5 km South - South-West, on the Sebeș River terraces.